Enhancing Knowledge Production through the Management of Technology and Innovation in Higher Education: Challenges and Opportunities - Ajani, Oluwatoyin Ayodele (CV. Literasi Indonesia, 2025)
This study explores the enhancement of knowledge production in higher education through the effective management of technology and innovation. Using a scoping review methodology, 278 articles were accessed from both Scopus and Google Scholar. Of these, only 68 peer-reviewed articles published in English were selected for thematic analysis. The review focused on identifying key challenges and opportunities related to technology and innovation management within higher education institutions. The analysis revealed several core challenges, including limited resources, cultural resistance, skill gaps, and concerns around data privacy and sustainability. Despite these obstacles, significant opportunities were identified. These include the potential for personalised learning, the use of artificial intelligence (AI) in research, enhanced global collaboration, and improvements in accessibility and administrative efficiency. Furthermore, the role of innovation hubs and public-private partnerships in fostering interdisciplinary research and development emerged as critical areas of focus. The findings underscore the importance of strategic leadership, policy development, and continuous evaluation in successfully managing technological innovation in higher education. By addressing these challenges and seizing the identified opportunities, institutions can play a pivotal role in advancing knowledge production and contributing to broader societal progress.